The Contribution of Teacher Support to Students’ Willingness to Communicate (WTC) in English Classes - Suci Maharani; Nita Kaniadewi (Jurnal Studi Guru dan Pembelajaran, 2026)
Students’ willingness to communicate (WTC) is considered an important factor in English as a Foreign Language (EFL) learning because it reflects students’ readiness to participate in communication activities. However, many vocational high school students still show low participation and lack confidence in communicating in English. One factor assumed to contribute to this issue is teacher support. Therefore, this study aimed to investigate the contribution of teacher support to students’ willingness to communicate in English classes at a vocational high school. This study employed a quantitative correlational design involving 140 tenth-grade students at SMKN 41 Jakarta. The data were collected through Likert-scale questionnaires measuring teacher support and students’ willingness to communicate. The Teacher Support instrument consisted of 20 valid items with a Cronbach’s Alpha value of 0.930, while the WTC instrument consisted of 18 valid items with a Cronbach’s Alpha value of 0.899 after two invalid items were removed through validity testing. The data were analyzed using descriptive statistics, normality testing, Spearman Rank Correlation, and simple linear regression in IBM SPSS Statistics. The findings revealed that the data were not normally distributed; therefore, Spearman Rank Correlation was used. The correlation analysis showed a significant positive relationship between teacher support and students’ willingness to communicate with a correlation coefficient of 0.310 and a significance value of 0.000. In addition, the simple linear regression analysis indicated that teacher support contributed positively and significantly to students’ willingness to communicate with an R Square value of 0.160, meaning that teacher support contributed 16% to students’ willingness to communicate. These findings imply that supportive teacher behavior may help students become more confident, motivated, and willing to communicate in English classes. The study also suggests that teachers should create more supportive and interactive classroom environments to improve vocational students’ participation in English communication activities.